Pengaruh Komitmen dan Perbedaan Generasi terhadap Kinerja Pegawai pada Badan Pendapatan Daerah Kabupaten Morowali Utara - Yesi Rohimah; Niluh Putu Evvy Rossanty; Yoberth Kornelius; Moh. Zeylo Auriza (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of commitment and generational differences on employee performance at the North Morowali Regency Revenue Agency. This is a quantitative study that identifies the independent variables, namely commitment and generational differences, and the dependent variable, namely performance, with a sample size of 63 people. The sampling technique used was saturated sampling, where all members of the population were included in the sample if the population size was relatively small, less than 30 people. A saturated sample is referred to as a census. The results of this study show that: 1) Based on the results of hypothesis testing, it is known that the variables of Commitment (X1) and Generational Differences (X2) have a significant effect on employee performance at the Regional Revenue Agency of North Morowali Regency. 2) Commitment has a positive and significant effect on employee performance at the Regional Revenue Agency of North Morowali Regency. 3) Generational Differences have a positive and significant effect on employee performance at the Regional Revenue Agency of North Morowali Regency.